Chlormethiazole in the treatment of neonatal status epilepticus. Issue 698 (December 1983) - Miller, P.; Kovar, I.
Abstract : A pre-term neonate with status epilepticus resistant to conventional treatment but who responded to a chlormethiazole infusion is reported. Nineteen days of continuous infusion was required before treatment could be discontinued and oral phenytoin substituted. Chlormethiazole should be considered in the treatment of resistant convulsions in the newborn.